The History of Istiwa’ in the Development of Islamic Falak - Achmad Mauludy Zahron; Ahmad Izzuddin; Eman Sulaiman (University of Muhammadiyah Sumatera Utara, 2026)
The history of istiwa’ represents one of the oldest scientific heritages in the history of astronomy, marking the position of the sun directly overhead, where the shadow of a vertical object becomes minimal or disappears. Since the civilizations of Egypt and Babylonia, this method has been used to regulate time and determine geographical directions. It was later refined by Greek scholars and eventually Islamized by Muslim astronomers as an instrument of falak (miqyāsal-zill) to determine prayer times and the direction of the qiblah. This study employs a qualitative method with a library research approach, examining classical sources such as al-Qānūn al-Mas'ūdī by al-Bīrūnī and modern literature on Rashdul Qiblah. The analysis was conducted descriptively and comparatively to trace the epistemological continuity between classical traditions and contemporary practices. The findings reveal that the concept of istiwa’ evolved from empirical observation into a theoretical falak system that integrates scientific and theological dimensions. Despite the advancement of digital technologies, the shadow-based observation method remains relevant for its accuracy and spiritual value. Future research is encouraged to explore the recontextualization of istiwa’ in modern falak education to strengthen the integration of science, faith, and ecological awareness within Islamic religious practices today.